Metahewettite, Ca(V5+6O16)(H2O)3, from Hodzha-Rushnai-Mazar, southern Kirgizia: occurrence and crystal structure - Cooper,M.A.; Hawthorne,F.C.; Karpenko,V.Y.; Pautov,L.A.; Agakhanov,A.A. (Journal of Geosciences, 2014)
Metahewettite was encountered in hypergene crusts in Paleozoic carbon-silica schists included in the carbon melange matrix at Hodzha-Rushnai-Mazar in southern Kirgizia. Schist outcrops are marked by multicolored yellow, orange, brown and green crusts of vanadates and sulfates of chalсoalumite group, volborthite, V-bearing phosphates, Cr-V-bearing members of alunite subgroup, members of the pascoite group and vanadium-bronze oxides, including metahewettite. Metahewettite is acicular with individual crystals up to 1 mm in length, and forms radial aggregates 2-3 mm diameter, or flattened aggregates in a narrow fissures. Crystals are dark-brown to reddish-brown with a golden sheen. The crystal structure of metahewettite, Ca(V5+6O16)(H2O)3, monoclinic, a = 12.208(5), b = 3.6011(15), c = 18.358(7) Å, β = 118.538(8)°, V = 709.0(8) Å3, Z = 2, A2/m, was refined to an R1 index of 2.4 % based on 1047 unique observed (Fo > 4σF) reflections. Electron-microprobe analysis (EDS) showed no detectable constituents apart from Ca and V, and the scattering from each site in the structure is conformable with the ideal composition Ca(V6O16)(H2O)3. There are three V sites in the structure with scattering in accord with their complete occupancy by V. The V(1) site is [5]-coordinated by O2- anions with a distance of 1.823 Å and a [2 + 3] arrangement of vanadyl and equatorial () bonds. The V(2) and V(3) sites are coordinated by O2- anions with distances of 1.934 and 1.916 Å and [2 + 2 + 2] and [1 + 4 + 1] arrangements of vanadyl , equatorial and trans bonds, respectively. The V(1) square pyramids share edges and vertices to form chains extending parallel to b with a repeat distance of 3.6 Å. The V(2) and V(3) octahedra share edges and vertices to form ribbons also extending parallel to b. The chains and ribbons link by sharing polyhedron corners to form sheets of V polyhedra parallel to (001). These sheets are linked by interlayer Ca that occupies two interstitial Ca sites, and by (H2O) groups.
Keywords: metahewettite; crystal structure; vanadium-bronze oxide; occurrence; Kirgizia